Family Law Transformation: Addressing Forced Child Marriage as a Criminal Offense in Indonesia - Fauziati, Fauziati; Abbas , Syahrizal; Zainuddin , Muslim (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2024)
Forced child marriage is a form of punishment following the enactment of Law Number 12 of 2022 concerning the Crime of Sexual Violence. The presence of this law has given a new nuance to changes in marriage law in Indonesia. This research aims to analyze the existence of Islamic marriage law reform in Indonesia through the prosecution of perpetrators of forced child marriages and the juridical implications for mujbir guardians in marriage. This research uses a type of normative legal research because the author analyzes the legal norms contained in the TPKS Law in the context of reforming Islamic family law and the juridical implications of the existence of this Law on the authority of mujbir guardians in marrying off children. Data was obtained by studying literature, materials in libraries, journals and research results. The primary legal materials used consist of the TPKS Law, the Marriage Law. Secondary legal materials are books, journals and research results, while tertiary legal materials are legal dictionaries and Islamic law encyclopedias. The research results show that the presence of the TPKS Law is a concrete answer to the problems faced by children, especially forced marriages that occur in society. The determination of punishment in cases of forced marriage is a form of ta'zir punishment and can be justified in Islamic teachings with the aim of realizing the benefit of children and ensuring the realization of maqashid syari'ah. The presence of the TPKS Law has contributed to efforts to reform Islamic family law. Guardians who force child marriages can be subject to imprisonment. The juridical implication for mujbir guardians is that they cannot marry off their underage daughters without the consent of the daughter being married.  Pemaksaan perkawinan anak merupakan bentuk pemidanaan pasca lahirnya UU Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual. Hadirnya UU tersebut telah memberikan nuansa baru terhadap perubahan hukum perkawinan di Indonesia. Penelitian ini bertujuan untuk menganalisis eksistensi pembaharuan hukum perkawinan Islam di Indonesia melalui pemidaan terhadap Pelaku pemaksaan perkawinan anak dan implikasi yuridis terhadap wali mujbir dalam perkawinan. Penelitian ini menggunakan jenis penelitian hukum normatif karena penulis menganalisis norma hukum yang terdapat dalam UU TPKS dalam konteks pembaharuan hukum keluarga Islam dan implikasi yuridis keberadaan UU tersebut terhadap kewenangan wali mujbir dalam menikahkan anak. data diperoleh dengan cara studi literatur bahan di perpustakaan, jurnal dan hasil penelitian. Bahan hukum primer yang digunakan terdiri dari UU TPKS, UU Perkawinan. Bahan hukum sekunder yaitu buku, jurnal dan hasil penelitian, sedangkan bahan hukum tersier yaitu kamus hukum dan ensiklopedia hukum Islam. Hasil penelitian menunjukkan bahwa hadirnya UU TPKS merupakan jawaban konkrit terhadap permasalahan yang dihadapi oleh anak khususnya pemaksaan perkawinan yang terjadi di tengah-tengah masyarakat. Penetapan hukuman pada kasus pemaksaan perkawinan merupakan bentuk hukuman ta’zir dan dapat dibenarkan dalam ajaran Islam dengan tujuan untuk mewujudkan kemaslahatan bagi anak serta menjamin terwujudnya maqashid syari’ah. Hadirnya UU TPKS telah berkontribusi dalam upaya pembaharuan hukum keluarga Islam. wali yang memaksakan perkawinan anak dapat dikenakan dengan hukuman penjara. Implikasi yuridis bagi wali mujbir yaitu tidak dapat menikahkan anak perempuannya yang masih di bawah umur tanpa persetujuan dari anak perempuan yang dinikahkan.